2021
DOI: 10.5194/bg-18-1525-2021
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the productivity of tropical Andean forests: climate and soil are more important than tree diversity

Abstract: Abstract. Theory predicts positive effects of species richness on the productivity of plant communities through complementary resource use and facilitative interactions between species. Results from manipulative experiments with tropical tree species indicate a positive diversity–productivity relationship (DPR), but the existing evidence from natural forests is scarce and contradictory. We studied forest aboveground productivity in more than 80 humid tropical montane old-growth forests in two highly diverse An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 83 publications
2
20
0
Order By: Relevance
“…Second, DPR is related to the definition of plant community productivity. Previous research showed that the relationship between species diversity and productivity was weak when only tree productivity was considered, but the relationship between species diversity and productivity was obvious when litter productivity was added (Homeier and Leuschner 2021). In this study, the productivity of forest trees was calculated, but litter productivity was not assessed.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Second, DPR is related to the definition of plant community productivity. Previous research showed that the relationship between species diversity and productivity was weak when only tree productivity was considered, but the relationship between species diversity and productivity was obvious when litter productivity was added (Homeier and Leuschner 2021). In this study, the productivity of forest trees was calculated, but litter productivity was not assessed.…”
Section: Discussionmentioning
confidence: 96%
“…Controlled experiments have shown a positive relationship between species diversity and productivity (Huang 2018;Schnabel et al 2019). However, these results are difficult to extrapolate to subtropical old-growth forests due to the young age of these tree plantations (Homeier and Leuschner 2021). Thus, the relationship between species diversity and productivity in natural communities is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive relationship between species richness and productivity is a result of efficient resource use by a diversity of species because of niche differentiation and facilitation (Loreau et al, 2001). In a recent study by Homeier and Leuschner (2021), in a highly species-rich Neotropical montane forest, productivity was primarily controlled by thermal and edaphic factors, and stand structure properties, while diversity had only a minor effect.…”
mentioning
confidence: 99%